The Viral Replication Complex Is Associated with the Virulence of Newcastle Disease Virus - Dortmans, J. C. F. M. (American Society for Microbiology (ASM), 2010)
Virulent strains of Newcastle disease virus ([NDV] also known as avian paramyxovirus type 1) can be discriminated from low-virulence strains by the presence of multiple basic amino acid residues at the proteolytic cleavage site of the fusion (F) protein. However, some NDV variants isolated from pigeons (pigeon paramyxovirus type 1 [PPMV-1]) have low levels of virulence, despite the fact that their F protein cleavage sites contain a multibasic amino acid sequence and have the same functionality as that of virulent strains. To determine the molecular basis of this discrepancy, we examined the role of the internal proteins in NDV virulence. Using reverse genetics, the genes encoding the nucleoprotein (NP), phosphoprotein (P), matrix protein (M), and large polymerase protein (L) were exchanged between the nonvirulent PPMV-1 strain AV324 and the highly virulent NDV strain Herts. Recombinant viruses were evaluated for their pathogenicities and replication levels in day-old chickens, and viral genome replication and plaque sizes were examined in cell culture monolayers. We also tested the contributions of the individual NP, P, and L proteins to the activity of the viral replication complex in an in vitro replication assay. The results showed that the replication proteins of Herts are more active than those of AV324 and that the activity of the viral replication complex is directly related to virulence. Although the M protein affected viral replication in vitro, it had only a minor effect on virulence.